Magnetic field enhanced convective diffusion of iron oxide nanoparticles in an osmotically disrupted cell culture model of the blood–brain barrier - Sun Z (Dove Medical Press, 2014)
Zhizhi Sun,1 Matthew Worden,2 Yaroslav Wroczynskyj,3 Vinith Yathindranath,4 Johan van Lierop,3 Torsten Hegmann,1,2,4,5 Donald W Miller1 1Department of Pharmacology and Therapeutics, University of Manitoba, Winnipeg, Manitoba, Canada; 2Department of Chemistry and Biochemistry, Kent State University, Kent, OH, USA; 3Department of Physics and Astronomy, 4Department of Chemistry, University of Manitoba, Winnipeg, Manitoba, Canada; 5Chemical Physics Interdisciplinary Program, Liquid Crystal Institute, Kent State University, Kent, OH, USA Purpose: The present study examines the use of an external magnetic field in combination with the disruption of tight junctions to enhance the permeability of iron oxide nanoparticles (IONPs) across an in vitro model of the blood–brain barrier (BBB). The feasibility of such an approach, termed magnetic field enhanced convective diffusion (MFECD), along with the effect of IONP surface charge on permeability, was examined. Methods: The effect of magnetic field on the permeability of positively (aminosilane-coated [AmS]-IONPs) and negatively (N-(trimethoxysilylpropyl)ethylenediaminetriacetate [EDT]-IONPs) charged IONPs was evaluated in confluent monolayers of mouse brain endothelial cells under normal and osmotically disrupted conditions. Results: Neither IONP formulation was permeable across an intact cell monolayer. However, when tight junctions were disrupted using D-mannitol, flux of EDT-IONPs across the bEnd.3 monolayers was 28%, increasing to 44% when a magnetic field was present. In contrast, the permeability of AmS-IONPs after osmotic disruption was less than 5%. The cellular uptake profile of both IONPs was not altered by the presence of mannitol. Conclusions: MFECD improved the permeability of EDT-IONPs through the paracellular route. The MFECD approach favors negatively charged IONPs that have low affinity for the brain endothelial cells and high colloidal stability. This suggests that MFECD may improve IONP-based drug delivery to the brain. Keywords: drug delivery, iron oxide nanoparticles, permeability, blood–brain barrier, magnetic targeting